2017
DOI: 10.1002/rmb2.12047
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the pathological process in endometriosis

Abstract: BackgroundEndometriosis is one of the most common gynecological diseases that greatly compromises the quality of life in affected individuals. A growing body of evidence shows that the remodeling of retrograde endometrial tissues to the ectopic endometriotic lesions involves multiple epigenetic alterations, such as DNA methylation, histone modification, and microRNA expression.MethodsThis article retrospectively reviewed the studies that were related to the epigenetic regulatory factors that contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
77
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 47 publications
0
77
0
4
Order By: Relevance
“…Accumulating evidence indicates that endometriosis is an epigenetic disease . Despite the identical genetic background between eutopic and ectopic endometrial cells in patients with endometriosis, numerous studies reported that significant differences in the biochemical properties of these two tissues exist.…”
Section: Hypoxia‐mediated Epigenetic Regulationmentioning
confidence: 99%
“…Accumulating evidence indicates that endometriosis is an epigenetic disease . Despite the identical genetic background between eutopic and ectopic endometrial cells in patients with endometriosis, numerous studies reported that significant differences in the biochemical properties of these two tissues exist.…”
Section: Hypoxia‐mediated Epigenetic Regulationmentioning
confidence: 99%
“…Inflammation induces DNMT3a expression and locus-specific hypermethylation. MiRNA-20a induced by hypoxia and miRNA302a induced by inflammatory cytokines both contribute to modulation of DNA methylation (HSIAO, et al 2017).…”
Section: Epigenetic Mechanisms In Endometriosis and Polycystic Ovary mentioning
confidence: 99%
“…Согласно современным представлениям, важное значение в развитии эндометриоза наряду с генетическими факторами играют и эпигенетические механизмы (уровень мети лирования ДНК, модификации гистоновых белков, регуляторные некодирующие РНК (non-coding RNAs)) [28][29][30][31][32][33][34][35][36].…”
unclassified
“…При сравнительном исследовании эктопического и эутопического эндометрия выявлена связь модификации гистонов с продукцией белков HDAC1, SUV39H1, SUV39H2, G9a, некоторых изоформ HDAC5 в очагах эндометриоза [28,32,33]. В исследованиях последних лет установлена значимая роль в развитии эндометриоза некодирующих РНК (noncoding RNAs), в частности микро-РНК (miRNAs) [34][35][36]. Эти РНК участвуют в регуляции воздействия стероидных гормонов на эндометрий.…”
unclassified
See 1 more Smart Citation